A comparative study of digital lateral radiography and virtual cone-beam computed assisted cephalogram in cephalometric measurements - Calle-Morocho, Jesica (2018)
Objectives: To assess discrepancies in cephalometric measurements from digital lateral radiography and virtual cone-beam computed assisted tomography cephalogram. Materials and methods: Forty digital lateral radiographs and forty virtual cephalograms obtained by cone-beam computed assisted tomography were analyzed, corresponding to forty patients from the nstituto de Diagnóstico Maxilofacial in Lima, Peru. The principal investigator, who had been previously calibrated, made two measurements within a timespan of fifteen days using the analysis of Steiner and the NemoCeph software, and the difference between the obtained measurements was evaluated to determine if it was significant. Results: For digital lateral radiographs the difference varied between 0.00º - 0.45º and 0.01mm - 0.16mm, with statistical significance for distance between Pg and NB for lateral virtual cephalograms between 0.03º - 0.73º and 0.01mm - 0.43mm, with statistical significance for SE distance. The comparison between the two types of image in the first measurement showed a difference of 0.08º - 1.15º and 0.00mm - 1.43mm with statistical significance for four angular measurements and one linear. The comparison between the two types of image in the second measurement showed a difference of 0.13º - 1º and 0.02mm - 1.32mm with a statistically significant difference for three angular and two linear measurements. Conclusions: The difference between the two types of image is minimal; Both evaluated methods can be used effectively.